Enhancing ESL learner’s literacy by peer-assisted learning strategy of online English news - Gong, Wen (Frontiers in Psychology, 2023)
As a result of globalization, countries are collaborating more and sharing more information. People’s perspectives now encompass both domestic and international news. In English as a Second Language (ESL) classes, the appropriate use of rich and vibrant online English news resources gives second language learners (L2 learners) direct access to first-hand, authentic English knowledge through independent reading and digestion, as well as peer-assisted classroom activities. Through weekly peer-assisted sharing of online English news, the goal of this study is to improve L2 learners’ literacy, global competence, and appreciation of cultural diversity. This study examines the participants’ perceptions and feedback using both quantitative and qualitative methods to confirm the efficacy of this pedagogy. After the semester-long experiment, significant differences were found in the English proficiency test. Particularly, the experimental class’s reading and writing scores were significantly higher (p < 0.05) than the control class’s, indicating that this pedagogy can effectively improve the literacy of ESL learners. The semi-structured interview revealed that participants were pleased with this instruction and perceived improvements in their language skills. ESL students’ core English literacy has significantly improved by expanding their comprehension of news articles and cultivating a sense of social responsibility.